Smartphone Addiction, Executive Function, and Mother-Child Relationships in Early Childhood Emotion Dysregulation - Warmansyah, Jhoni; Ismandela, Afriyane; Fatma Nabila, Dinda; Wulandari, Retno; Putri Wahyu, Widia; Khairunnisa; putri, Anis; Komalasari, Elis; Sari, Meliana; Yuningsih, Restu; Masril, Masril (Program Studi Magister Pendidikan Anak Usia Dini, 2023)
Early childhood emotional dysregulation is critical in recognizing and preventing psychological well-being disorders, laying the groundwork for developing healthy emotional behaviors early on. This study aims to determine the direct influence of smartphone addiction, executive function, and the mother-child relationship on emotional dysregulation in early childhood in West Sumatra. This research method is a quantitative survey. The data collection technique in this research uses a questionnaire design on 309 parents who were selected using a simple random sampling method. This data processing tool uses the SmartPLS software. The results of the study indicate that smartphone addiction has a significant impact on emotional dysregulation in early childhood, executive function has a positive and significant effect on emotional dysregulation in early childhood, and the mother-child relationship has a positive and significant influence on emotional dysregulation in early childhood. The findings of this research can offer valuable insights into improving the understanding of the factors that influence emotional dysregulation in early childhood and intervention strategies to address the issues that arise as a result. Keywords: smartphone addiction, executive function, mother-child relationship, emotional dysregulation, early childhood References: Aisyah, Salehudin, M., Yatun, S., Yani, Komariah, D. L., Aminda, N. E. R., Hidayati, P., & Latifah, N. (2021). Persepsi Orang Tua Dalam Pendidikan karakter Anak Usia Dini Pada Pembelajaran Online di Masa Pandemi Covid-19. PEDAGOGI: Jurnal Anak Usia Dini Dan Pendidikan Anak Usia Dini, 7(1), 60–75. https://doi.org/http://dx.doi.org/10.30651/pedagogi.v7i1.6593 Allison, S. Z. (2023). Islamic Educational Provisions in South Korea and Indonesia : A Comparison. Journal of Islamic Education Students, 3, 50–61. https://doi.org/10.31958/jies.v3i1.8772 Anggraini, E. (2019). Mengatasi Kecanduan Gadget Pada Anak. Serayu Publishing. Annisa, N., Padilah, N., Rulita, R., & Yuniar, R. (2022). Dampak Gadget Terhadap Perkembangan Anak Usia Dini. Jurnal Pendidikan Indonesia, 3(9), 837–849. https://doi.org/10.36418/japendi.v3i9.1159 Annisavitry, Y., & Budiani, M. S. (2006). Hubungan antara Kematangan Emosi dengan Agresivitas pada Remaja. 1–6. Anzani, R. W., & Intan Khairul Insan. (2020). Perkembangan sosial emosi pada anak usia prasekolah. Jurnal Pendidikan Dan Dakwah, 02, 180–193. APJII. (2019). Pengguna Internet Indonesia Hampir Tembus 200 Juta di 2019. Asosiasi Pengguna Jasa Internet Indonesia (APJII). https://blog.apjii.or.id/index.php/2020/11/09/siaran-pers-pengguna-internet-indonesia-hampir-tembus-200-juta-di-2019-q2-2020/ Aryanti, Z. (2017). Kelekatan dalam perkembangan anak. Arbawiyah: Jurnal Ilmiah Pendidikan. Ashari, L. F., & Anwar, F. (2022). Moral Problems and Mothers’ Efforts to Educate Children in Single Parent Families. Journal of Islamic Education Students (JIES), 2(1), 12. https://doi.org/10.31958/jies.v2i1.4367 Ayomi, A. T. R., Widyorini, E., & Roswita, M. Y. (2021). Hubungan Inteligensi dengan Fungsi Eksekutif pada Anak Gifted Relationship between Intelligence and Executive Function to Gifted Children. Jurnal Ilmiah Psikologi Candrajiwa, 6(2), 136. Bachtiar, M. A., & Faletehan, A. F. (2021). Self-Healing sebagai Metode Pengendalian Emosi. Journal An-Nafs: Kajian Penelitian Psikologi, 6(1), 41–54. https://doi.org/10.33367/psi.v6i1.1327 Baptista, J., Osório, A., Martins, E. C., Verissimo, M., & Martins, C. (2016). Does social-behavioral adjustment mediate the relation between executive function and academic readiness? Journal of Applied Developmental Psychology, 46, 22–30. https://doi.org/10.1016/j.appdev.2016.05.004 Bassett, H. H., Denham, S., Wyatt, T. M., & Warren-Khot, H. K. (2012). Refining the Preschool Self-regulation Assessment for Use in Preschool Classrooms. Infant and Child Development, 21(6), 596–616. https://doi.org/10.1002/icd.1763 Bell, M. A., & Wolfe, C. D. (2004). Emotion and Cognition: An Intricately Bound Developmental Process. Child Development, 75(2), 366–370. https://doi.org/10.1111/j.1467-8624.2004.00679.x Bocknek, E. L., Brophy-Herb, H. E., Fitzgerald, H., Burns-Jager, K., & Carolan, M. T. (2012). Maternal Psychological Absence and Toddlers’ Social-Emotional Development: Interpretations From the Perspective of Boundary Ambiguity Theory. Family Process, 51(4), 527–541. https://doi.org/10.1111/j.1545-5300.2012.01411.x Brock, R. L., & Kochanska, G. (2019). Anger in infancy and its implications: History of attachment in mother–child and father–child relationships as a moderator of risk. Development and Psychopathology, 31(04), 1353–1366. https://doi.org/10.1017/S0954579418000780 Cacioppo, J. T., & Berntson, G. G. (2019). The Affect System structure: architecture and operating characteristics. Current Directions in Psychological Science, 8(5), 133–137. https://doi.org/10.1111/1467-8721.00031 Calkins, S. D., & Marcovitch, S. (2015). Emotion regulation and executive functioning in early development: Integrated mechanisms of control supporting adaptive functioning. In Child development at the intersection of emotion and cognition. (pp. 37–57). American Psychological Association. https://doi.org/10.1037/12059-003 Carlson, S. M. (2005). Developmentally Sensitive Measures of Executive Function in Preschool Children. Developmental Neuropsychology, 28(2), 595–616. https://doi.org/10.1207/s15326942dn2802_3 Chang, F.-C., Chiu, C.-H., Chen, P.-H., Chiang, J.-T., Miao, N.-F., Chuang, H.-Y., & Liu, S. (2019). Children’s use of mobile devices, smartphone addiction and parental mediation in Taiwan. Computers in Human Behavior, 93, 25–32. https://doi.org/10.1016/j.chb.2018.11.048 Chiu, S.-I. (2014). The relationship between life stress and smartphone addiction on taiwanese university student: A mediation model of learning self-Efficacy and social self-Efficacy. Computers in Human Behavior, 34, 49–57. https://doi.org/10.1016/j.chb.2014.01.024 Cholik, C. A. (2021). Perkembangan Teknologi Informasi Komunikasi / Ict Dalam Berbagai Bidang. Jurnal Fakultas Teknik, 14, 1–13. Chusna, P. A. (2017). Pengaruh Media Gadget pada Perkembangan Karakter Anak. 315–330. Cole, P. M., Martin, S. E., & Dennis, T. A. (2004). Emotion Regulation as a Scientific Construct: Methodological Challenges and Directions for Child Development Research. Child Development, 75(2), 317–333. https://doi.org/10.1111/j.1467-8624.2004.00673.x Denham, S. A., Ferrier, D. E., Howarth, G. Z., Herndon, K. J., Bassett, H. H., Denham, S. A., Ferrier, D. E., Howarth, G. Z., & Herndon, K. J. (2016). Key considerations in assessing young children ’ s emotional competence. Cambridge Journal of Education ISSN:, 3577(April). https://doi.org/10.1080/0305764X.2016.1146659 Eliasa, E. I. (2011). Pentingnya kelekatan orangtua dalam internal working model untuk pembentukan karakter anak (kajian berdasarkan teori kelekatan dari john bowlby). Yogyakarta: Inti Media Yogyakarta Bekerjasama Dengan Pusat Studi Pendidikan Anak Usia Dini Lembaga Penelitian Universitas Negeri Yogyakarta. Evy Clara, A. A. D. W. (2020). Sosiologi Keluarga. In UNJ PRESS. Unj Press. Fatwikiningsih, N. (2016). Rehabilitasi Neuropsikologi Dalam Upaya Memperbaiki Defisit Executive Function (Fungsi Eksekutif) Klien Gangguan Mental. Journal An-Nafs: Kajian Penelitian Psikologi, 1(2), 320–335. https://doi.org/10.33367/psi.v1i2.296 Ferrier, D. E., Bassett, H. H., & Denham, S. A. (2014). Relations between executive function and emotionality in preschoolers: Exploring a transitive cognitionâ€“emotion linkage. Frontiers in Psychology, 5. https://doi.org/10.3389/fpsyg.2014.00487 Ferrier, D. E., Karalus, S. P., Denham, S. A., Hideko, H., Ferrier, D. E., Karalus, S. P., Denham, S. A., & Bassett, H. H. (2018). Indirect effects of cognitive self-regulation on the relation between emotion knowledge and emotionality between emotion knowledge and emotionality. Early Child Development and Care, 0(0), 1–14. https://doi.org/10.1080/03004430.2018.1445730 Flannery, D. D., Gouma, S., Dhudasia, M. B., Mukhopadhyay, S., Pfeifer, M. R., Woodford, E. C., Triebwasser, J. E., Gerber, J. S., Morris, J. S., Weirick, M. E., McAllister, C. M., Bolton, M. J., Arevalo, C. P., Anderson, E. M., Goodwin, E. C., Hensley, S. E., & Puopolo, K. M. (2021). Assessment of Maternal and Neonatal Cord Blood SARS-CoV-2 Antibodies and Placental Transfer Ratios. JAMA Pediatrics, 175(6), 594. https://doi.org/10.1001/jamapediatrics.2021.0038 Gio, P. U. (2019). Covariance-Based Structural Equation Modeling(CB-SEM) dengan Disertai Perbandingan Hasil dengan Software LISREL dan Amos. In STATCAL (pp. 1–56). Statkomat. www.statcal.org Gioia, G. A., Isquith, P. K., Guy, S. C., & Kenworthy, L. (2000). TEST REVIEW Behavior Rating Inventory of Executive Function. Child Neuropsychology, 6(3), 235–238. https://doi.org/10.1076/chin.6.3.235.3152 Goleman, D. (2015). Emotional Intelligence. PT. Main Library Gramedia. Groves, N. B., Wells, E. L., Soto, E. F., Marsh, C. L., Jaisle, E. M., Harvey, T. K., & Kofler, M. J. (2022). Executive Functioning and Emotion Regulation in Children with and without ADHD. Research on Child and Adolescent Psychopathology, 50(6), 721–735. https://doi.org/10.1007/s10802-021-00883-0 Guswani, A. M. (2011). Perilaku agresi pada mahasiswa ditinjau dari kematangan emosi. I(2), 86–92. Hadi, S. (2011). Pembelajaran Sosial Emosional Sebagai Dasar Pendidikan Karakter Anak Usia Dini. Jurnal Teknodik, 15(2), 227–240. Hadi, S. (2013). Pembelajaran Sosial Emosional Sebagai Dasar Pendidikan Karakter Anak Usia Dini. Jurnal Teknodik, 227–240. https://doi.org/10.32550/teknodik.v0i0.104 Handayani, S., Sumarno, S., & Haryati, Y. (2017). UpayaMeningkatkan Kemampuan Kognitif Dalam Memperkenalkan Konsep Pengukuran Anak Usia Dini Melalui Metode Bermain Peran. Jurnal Karya Pendidikan Matematika, 4(1), 43. https://doi.org/10.1017/CBO9781107415324.004 Hapsari. (2016). Psikologi Perkembangan Anak. PT Index. Hasanah, M. (2017). Pengaruh Gadget terhadap Kesehatan Mental Anak. 2(2), 207–214. Hermawati, N. S., & Sugito, S. (2021). Peran Orang Tua dalam Menyediakan Home Literacy Environment (HLE) pada Anak Usia Dini. Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 6(3), 1367–1381. https://doi.org/10.31004/obsesi.v6i3.1706 Herndon, K. J., Bailey, C. S., Shewark, E. A., Denham, S. A., & Bassett, H. H. (2013). Preschoolers’ Emotion Expression and Regulation: Relations with School Adjustment. The Journal of Genetic Psychology, 174(6), 642–663. https://doi.org/10.1080/00221325.2012.759525 Holley, S. R., Ewing, S. T., Stiver, J. T., & Bloch, L. (2015). The Relationship Between Emotion Regulation , Executive Functioning , and Aggressive Behaviors. Journal of Interpersonal Violence, 15(3), 1–16. https://doi.org/10.1177/0886260515592619 Imron, R. I. (2017). Hubungan Penggunaan Gadget Dengan Perkembangan Sosial Dan Emosional Anak Prasekolah Di Kabupaten Lampung Selatan. XIII(2), 148–154. Islamiah, A. (2018). Dampak teknologi informasi terhadap perilaku keagamaan bagi remaja di menganti gresik. Skrispi, Universita(Surabaya), 48. Ita, E., & Fono, Y. M. (2021). Pendampingan Kesulitan Belajar Pada Smartphone Addiction Child di PAUD Terpadu Citra Bakti. Jurnal Abdimas Ilmiah Citra Bakti, 2(2), 149–156. https://doi.org/10.38048/jailcb.v2i2.377 Jahromi, L. B., & Stifter, C. A. (2008). Individual Differences in Preschoolers’ Self-Regulation and Theory of Mind. Merrill-Palmer Quarterly, 54(1), 125–150. https://doi.org/10.1353/mpq.2008.0007 Joormann, J., & Quinn, M. E. (2014). Cognitive Processes And Emotion Regulation in Depression. Depression and Anxiety, 31(4), 308–315. https://doi.org/10.1002/da.22264 Jumrianti, F., Nugroho, S., & Arief, Y. (2022). Hubungan Antara Kecanduan Smartphone Dengan Psychological Well-being Pada Remaja. Journal of Islamic and Contemporary Psychology (JICOP), 2(1), 49–57. https://doi.org/10.25299/jicop.v2i1.10263 Kabali, H. K., Irigoyen, M. M., Nunez-Davis, R., Budacki, J. G., Mohanty, S. H., Leister, K. P., & Bonner, R. L. (2015). Exposure and Use of Mobile Media Devices by Young Children. Pediatrics, 136(6), 1044–1050. https://doi.org/10.1542/peds.2015-2151 Katz, E. (2019). Coercive Control, Domestic Violence, and a Five-Factor Framework: Five Factors That Influence Closeness, Distance, and Strain in Mother–Child Relationships. Violence Against Women, 25(15), 1829–1853. https://doi.org/10.1177/1077801218824998 Khoshgoftar, M., Khodabakhshi-Koolaee, A., & Sheikhi, M. R. (2022). Analysis of the early mother-child relationship in schizophrenic patients. International Journal of Social Psychiatry, 68(3), 548–554. https://doi.org/10.1177/0020764021991186 Kominfo. (2018). Indonesia Raksasa teknologi Digital Asia. Kominfo.Go.Id. https://www.kominfo.go.id/content/detail/6095/indonesia-raksasa-teknologi-digital-asia/0/sorotan_media Kujawa, A., Arfer, K. B., Finsaas, M. C., Kessel, E. M., Mumper, E., & Klein, D. N. (2020). Effects of Maternal Depression and Mother–Child Relationship Quality in Early Childhood on Neural Reactivity to Rejection and Peer Stress in Adolescence: A 9-Year Longitudinal Study. Clinical Psychological Science, 8(4), 657–672. https://doi.org/10.1177/2167702620902463 Kusdemawati, J. (2021). Dampak Attachment Ibu-Anak Bagi Perkembangan Dampak Attachment Ibu-Anak Bagi Perkembangan Psikososial Anak Di Masa Remaja Anak Di Masa Remaja. ROSYADA: Islamic Guidance and Counseling, 2(2), 141–148. https://doi.org/10.21154/rosyada.v2i2.3539 Kusramadhanty, M., Hastuti, D., & Herawati, T. (2019). Temperamen dan praktik pengasuhan orang tua menentukan perkembangan sosial emosi anak usia prasekolah. Persona:Jurnal Psikologi Indonesia, 8(2), 258–277. https://doi.org/10.30996/persona.v8i2.2794 Kusuma, T. C. (2015). Peningkatan Kemampuan Pengukuran Dalam Matematika Awal Melalui Metode Discovery Learning (Penelitian Tindakan Di Tk B Pertiwi I Kantor Gubernur Padang Tahun 2015). Jurnal Tumbuh Kembang, 4(1), 76–84. https://doi.org/https://doi.org/10.36706/jtk.v4i1.8242 Kwon, M., Lee, J.-Y., Won, W.-Y., Park, J.-W., Min, J.-A., Hahn, C., Gu, X., Choi, J.-H., & Kim, D.-J. (2013). Development and Validation of a Smartphone Addiction Scale (SAS). PLoS ONE, 8(2), e56936. https://doi.org/10.1371/journal.pone.0056936 Laible, D., Davis, A., Karahuta, E., & Van Norden, C. (2020). Does corporal punishment erode the quality of the mother–child interaction in early childhood? Social Development, 29(3), 674–688. https://doi.org/10.1111/sode.12427 Lauricella, A. R., Wartella, E., & Rideout, V. J. (2015). Young children’s screen time: The complex role of parent and child factors. Journal of Applied Developmental Psychology, 36, 11–17. https://doi.org/10.1016/j.appdev.2014.12.001 Lintuuran, rifo mario warouw. (2015). Hubungan antara Kadar Seng dalam Serum dengan Fungsi Eksekutif pada Anak dengan Gangguan Pemusatan Perhatian dan Hiperaktivitas (GPPH) Correlation between Serum Zinc Level and Executive Function in Children with Attention Deficit/Hyperactivity Disorder (A. 17(4), 285–291. Mansur, A. R. (2019). Tumbuh kembang anak usia prasekolah. In 1 (Ed.), Andalas University Pres. Martí, M., Bonillo, A., Jané, M. C., Fisher, E. M., & Duch, H. (2016). Cumulative Risk, the Mother–Child Relationship, and Social-Emotional Competence in Latino Head Start Children. Early Education and Development, 27(5), 590–622. https://doi.org/10.1080/10409289.2016.1106202 Martin, R. E., & Ochsner, K. N. (2016). The neuroscience of emotion regulation development : implications for education. Current Opinion in Behavioral Sciences, 10, 142–148. https://doi.org/10.1016/j.cobeha.2016.06.006 Martins, E. C., Mărcuș, O., Leal, J., Visu-petra, L., Costa, E., Mărcuș, O., Leal, J., Visu-petra, L., & Martins, E. C. (2018). Assessing hot and cool executive functions in preschoolers : affective flexibility predicts emotion regulation a ff ective fl exibility predicts emotion regulation. Early Child Development and Care, 0(0), 1–15. https://doi.org/10.1080/03004430.2018.1545765 Mawarpury, M. (2020). Kecenderungan Adiksi Smartphone ditinjau dari jenis kelamin dan usia. 05, 24–37. Miller, J. G., Vrtička, P., Cui, X., Shrestha, S., Hosseini, S. M. H., Baker, J. M., & Reiss, A. L. (2019). Inter-brain synchrony in mother-child dyads during cooperation: An fNIRS hyperscanning study. Neuropsychologia, 124, 117–124. https://doi.org/10.1016/j.neuropsychologia.2018.12.021 Miyake, A., Friedman, N. P., Emerson, M. J., Witzki, A. H., Howerter, A., & Wager, T. D. (2020). The Unity and Diversity of Executive Functions and Their Contributions to Complex “Frontal Lobe” Tasks: A Latent Variable Analysis. Cognitive Psychology, 41(1), 49–100. https://doi.org/10.1006/cogp.1999.0734 Mu’min, S. A. (2013). Teori Pengembangan Kognitif Jian Piaget. Jurnal AL-Ta’dib, 6(1), 89–99. Nikken, P., & Schols, M. (2015). How and Why Parents Guide the Media Use of Young Children. Journal of Child and Family Studies, 24(11), 3423–3435. https://doi.org/10.1007/s10826-015-0144-4 Nisak, F. F., Munawaroh, H., & Abbas, S. (2022). The Effect of “ Kids Moderations ” Interactive Multimedia on Religious Moderation Attitudes in Early Childhood. Indonesian Journal of Early Childhood Education Research, 1(1), 38–47. https://doi.org/10.31958/ijecer.v1i1.5811 Novitasari, W., & Khotimah, N. (2013). Dampak Penggunaan Gadget Terhadap Interksi Sosial Anak Usia 5-6 Tahun. 05(03), 182–186. Nurjannah, N. (2017). Mengembangkan Kecerdasan emosiaonal Anak Usia Dini Melalui Keteladanan. Hisbah: Jurnal Bimbingan Konseling Dan Dakwah Islam, 14(1), 50–61. https://doi.org/10.14421/hisbah.2017.141-05 Pangastuti, R. (2017). Fenomena Gadget dan Perkembangan Sosial bagi Anak Usia Dini. Ijiece, 2(2), 165–174. Park, C., & Park, Y. R. (2014). The Conceptual Model on Smart Phone Addiction among Early Childhood. International Journal of Social Science and Humanity, 4(2), 147–150. https://doi.org/10.7763/IJSSH.2014.V4.336 Peñacoba, C., & Catala, P. (2019). Associations Between Breastfeeding and Mother–Infant Relationships: A Systematic Review. Breastfeeding Medicine, 14(9), 616–629. https://doi.org/10.1089/bfm.2019.0106 Pérez-Salas, C. P., Ramos, C., Oliva, K., & Ortega, A. (2016). Bifactor modeling of the behavior rating inventory of executive function (BRIEF) in a Chilean sample. Perceptual and Motor Skills, 122(3), 757–776. https://doi.org/10.1177/0031512516650441 Pianta, R. C. (2001). Student-teacher relationship scale: Professional manual. Psychological Assessment Resources. Priyanti, N., & Jhoni Warmansyah. (2021). The Effect of Loose Parts Media on Early Childhood Naturalist Intelligence. JPUD - Jurnal Pendidikan Usia Dini, 15(2), 239–257. https://doi.org/10.21009/jpud.152.03 Putri, A. R. H., & Rahmasari, D. (2021). Disregulasi Emosi pada Perempuan Dewasa Awal yang Melakukan Self Injury. Character: Jurnal Penelitian Psikologi, 1–16. Putri, C. I. H., & Primana, L. (2018). Gambaran Perilaku Disregulasi Emosi Anak Prasekolah Usia 3-4 Tahun. Jurnal Ilmiah Psikologi Terapan, 6(1), 102. https://doi.org/10.22219/jipt.v6i1.5113 Rachmat, I. F., Hartati, S., & Erdawati. (2021a). Pengaruh Kecanduan Gawai Terhadap Disregulasi Emosi Anak Usia Dini. Journal of Chemical Information and Modeling, 53(9), 1689–1699. https://ojs3.umc.ac.id/index.php/JJB/article/view/1726 Rachmat, I. F., Hartati, S., & Erdawati, E. (2021b). Family Cohesion, Interpersonal Communication, and Smartphone Addiction: Does It Affect Children’s Emotional Dysregulation? Jurnal Cakrawala Pendidikan, 40(2), 279–291. https://doi.org/10.21831/cp.v40i2.34214 Radliya, N. R., Apriliya, S., & Zakiyyah, T. R. (2017). Pengaruh Penggunaan Gawai Terhadap Perkembangan Sosial Emosional Anak Usia Dini. Jurnal Paud Agapedia, 1(1), 1–12. https://doi.org/10.17509/jpa.v1i1.7148 Riggs, N. R., Jahromi, L. B., Razza, R. P., Dillworth-Bart, J. E., & Mueller, U. (2016). Executive function and the promotion of social–emotional competence. Journal of Applied Developmental Psychology, 27(4), 300–309. https://doi.org/10.1016/j.appdev.2006.04.002 Roberts, M. Z., Flagg, A. M., & Lin, B. (2022). Context matters: How smartphone (mis)use may disrupt early emotion regulation development. New Ideas in Psychology, 64, 100919. https://doi.org/10.1016/j.newideapsych.2021.100919 Rubinsztein, D. C., Gestwicki, J. E., Murphy, L. O., & Klionsky, D. J. (2007). Potential therapeutic applications of autophagy. Nature Reviews Drug Discovery, 6(4), 304–312. https://doi.org/10.1038/nrd2272 Safitri, N. D., Hasanah, U., & Masruroh, F. (2023). The Development of Thematic Board Educational Game Tools to Train The Literacy Skills of Children 5-6 Years Old. Indonesian Journal of Early Childhood Educational Research, 1(2), 75–86. https://doi.org/10.31958/ijecer.v1i2.8156 Salsabilafitri, N., & Izzati, I. (2022). Pelaksanaan Pengembangan Sosial Anak di Taman Kanak-kanak Pertiwi 1 Kantor Gubernur Padang. Jurnal Pendidikan AURA (Anak Usia Raudhatul Atfhal). https://doi.org/10.37216/aura.v3i1.591 Sandoval, J., & Echandia, A. (1994). Behavior assessment system for children. Journal of School Psychology, 32(4), 419–425. https://doi.org/10.1016/0022-4405(94)90037-X Santrock, J. W. (2008). Psikologi Pendidikan (terjemahan). Kencana Prenada Media Group. Saraswati, S. W. E., Setiawan, D., & Hilyana, F. S. (2021). Dampak Penggunaan Smartphone pada Perilaku Anak Di Desa Muktiharjo Kabupaten Pati. WASIS : Jurnal Ilmiah Pendidikan, 2(2), 96–102. https://doi.org/10.24176/wasis.v2i2.6432 Sari, I. P., Warmansyah, J., Yuningsih, R., & Sari, M. (2023). The Effect of Realistic Mathematics Education ( RME ) Learning Approach on the Ability to Recognize Number Concepts in Children Aged 4-5 Years. Journal of Islamic Education Students, 3, 38–49. https://doi.org/10.31958/jies.v3i1.8654 Schmeichel, B. J., & Tang, D. (2015). Individual Differences in Executive Functioning and Their Relationship to Emotional Processes and Responses. Current Directions in Psychological Science, 24(2). https://doi.org/10.1177/0963721414555178 Setianingsih, Ardani, A. W., & Khayati, F. N. (2018). Dampak Penggunaan Gadget Pada Anak Usia Prasekolah Dapat Meningkatan Resiko Gangguan Pemusatan Perhatian Dan Hiperaktivitas. XVI(2), 191–205. Shaffer, A. (2017). Unique Contributions of Emotion Regulation and Executive Functions in Predicting the Quality of Parent – Child Interaction Behaviors. Journal of Family Psychology, 31(2), 150–159. Shah, P. E., Weeks, H. M., Richards, B., & Kaciroti, N. (2018). Early childhood curiosity and kindergarten reading and math academic achievement. Pediatric Research, 84(3), 380–386. https://doi.org/10.1038/s41390-018-0039-3 Sirois, M.-S., Bernier, A., & Lemelin, J.-P. (2019). Child temperamental anger, mother–child interactions, and socio-emotional functioning at school entry. Early Childhood Research Quarterly, 47, 30–38. https://doi.org/10.1016/j.ecresq.2018.10.005 Siskawati & Herawati. (2021). Efektivitas Media Loose Parts di PAUD Kelompok A Pada Masa Belajar Dari Rumah. Jurnal Pendidikan Luar Sekolah, 15(1), 41–47. https://doi.org/10.32832/jpls.v14i2.4629 Smith-Donald, R., Raver, C. C., Hayes, T., & Richardson, B. (2007). Preliminary construct and concurrent validity of the Preschool Self-regulation Assessment (PSRA) for field-based research. Early Childhood Research Quarterly, 22(2), 173–187. https://doi.org/10.1016/j.ecresq.2007.01.002 Smith-Etxeberria, K., & Eceiza, A. (2021). Mother-Child and Father-Child Relationships in Emerging Adults from Divorced and Non-Divorced Families. Social Sciences, 10(10), 382. https://doi.org/10.3390/socsci10100382 Soetjiningsih. (2018). Seri Psikologi Perkembangan : Perkembangan Anak Sejak Pembuahan Sampai dengan Kanak-Kanak Akhir. Kencana. Solfiah, Y. S., Risma, D., Hukmi, & Kurnia, R. (2020). Early Childhood Disaster Management Media Through Picture Story Books. JPUD - Jurnal Pendidikan Usia Dini, 14(1), 141–155. https://doi.org/10.21009/141.10 Sucipto, & Huda, N. (2016). Pola Bermain Anak Usia Dini di Era Gadget Siswa PAUD Mutiara Bunda Sukodono Sidoarjo (pp. 274–347). Sundus. (2017). The Impact of using Gadgets on Children. Journal of Depression and Anxiety, 07(01). https://doi.org/10.4172/2167-1044.1000296 Susanti, D., & Hasmira, M. S. P. (2023). Peran fungsi eksekutif otak pada perkembangan anak. 4(01), 22–32. Trinika, Y. (2015). Pengaruh Penggunaan Gadgetterhadap Perkembangan Psikososial Anak Usia Prasekolah (3- 6 Tahun) Di Tk Swasta Kristen Immanuel Tahun Ajaran 2014-2015. Turk, C. L., Heimberg, R. G., Luterek, J. A., Mennin, D. S., & Fresco, D. M. (2005). Emotion dysregulation in generalized anxiety disorder: A comparison with social anxiety disorder. Cognitive Therapy and Research, 29(1), 89–106. https://doi.org/10.1007/s10608-005-1651-1 Ulfah, M. (2020). DIGITAL PARENTING: Bagaimana Orang Tua Melindungi Anak-anak dari Bahaya Digital? Edu Publisher. Ulya, L., Sucipto, S., & Fathurohman, I. (2021). Analisis Kecanduan Game Online Terhadap Kepribadian Sosial Anak. Jurnal Educatio FKIP UNMA, 7(3), 1112–1119. https://doi.org/10.31949/educatio.v7i3.1347 Unde, A. A., Fatimah, J. M., & Hasanuddin, U. (2023). Komunikasi orang tua pekerja dalam menjaga kesehatan mental anak. 4, 39–51. Ursache, A., Blair, C., & Raver, C. C. (2012). The Promotion of Self-Regulation as a Means of Enhancing School Readiness and Early Achievement in Children at Risk for School Failure. Child Development Perspectives, 6(2), 122–128. https://doi.org/10.1111/j.1750-8606.2011.00209.x Ursache, A., Blair, C., Stifter, C., & Voegtline, K. (2013). Emotional reactivity and regulation in infancy interact to predict executive functioning in early childhood. Developmental Psychology, 49(1), 127–137. https://doi.org/10.1037/a0027728 Valiente, C., Swanson, J., & Eisenberg, N. (2012). Linking Students’ Emotions and Academic Achievement: When and Why Emotions Matter. Child Development Perspectives, 6(2), 129–135. https://doi.org/10.1111/j.1750-8606.2011.00192.x Vgontzas, A. N., Lin, H.-M., Papaliaga, M., Calhoun, S., Vela-Bueno, A., Chrousos, G. P., & Bixler, E. O. (2008). Short sleep duration and obesity: the role of emotional stress and sleep disturbances. International Journal of Obesity, 32(5), 801–809. Wahyuni, A. S., Siahaan, F. B., Arfa, M., Alona, I., & Nerdy, N. (2019). The Relationship between the Duration of Playing Gadget and Mental Emotional State of Elementary School Students. Open Access Macedonian Journal of Medical Sciences, 7(1), 148–151. https://doi.org/10.3889/oamjms.2019.037 Warmansyah, J., Zulhendri, Z., & Amalina, A. (2021). The Effectiveness of Lore Traditional Games Towards The Ability to Recognize The Concept of Numbers on Early Childhood. Ta’dib, 24(2), 79. https://doi.org/10.31958/jt.v24i2.2685 Wilson, D., & Gross, D. (2018). Parents ’ Executive Functioning and Involvement in Their Child ’ s Education : An. Journal of School Health, 88(4), 322–329. Wulandani, C., & Putri, M. A. (2022). Implementing Project-Based Steam Instructional Approach in Early Childhood Education in 5 . 0 Industrial Revolution Era. 1(1), 29–37. https://doi.org/10.31958/ijecer.v1i1.5819 Yan, J., Schoppe-Sullivan, S. J., & Feng, X. (2019). Trajectories of mother-child and father-child relationships across middle childhood and associations with depressive symptoms. Development and Psychopathology, 31(04), 1381–1393. https://doi.org/10.1017/S0954579418000809 Yansyah, Y., Hamidah, J., & Ariani, L. (2021). Pengembangan Big Book Storytelling Dwibahasa untuk Meningkatkan Literasi Anak Usia Dini. Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 6(3), 1449–1460. https://doi.org/10.31004/obsesi.v6i3.1779 Yunianggraeni. (2019). Pengawasan Orang Tua Dalam Penggunaan Gadget Pada Anak Di Ra Yapsisumberjaya Lampung Barat. Skripsi, 561(3), S2–S3. Zaini, M., & Soenarto, S. (2019). Persepsi Orangtua Terhadap Hadirnya Era Teknologi Digital di Kalangan Anak Usia Dini. Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 3(1), 254. https://doi.org/10.31004/obsesi.v3i1.127 Zelazo, Z., Blair, P. D., B.W, C., & Illoughby, M. (2016). Executive Function: Implications for Education. NCER 2017-2000. National Center for Education Research, 1(2).